Short-term effects of PM1, PM2.5, and PM2.5 constituents on myocardial infarction mortality in qingdao, China: A time-stratified case-crossover analysis. (1st February 2023) - Ma, Xiaoyun; Duan, Haiping; Zhang, Hua; Liu, Xue; Sun, Xiaohui; Wei, Jing; Zhao, Min; Xi, Bo
Abstract: Myocardial infarction (MI) is a major global contributor to disability and death. Few studies have investigated the impacts of short-term exposure to particulate matter with an aerodynamic diameter ≤1 μm (PM1 ) and ≤2.5 μm (PM2.5 ) constituents on MI mortality. We aimed to estimate the risks of MI mortality related to short-term exposures to PM1, PM2.5, and PM2.5 constituents. Daily MI deaths, daily concentrations of PM1, PM2.5, PM2.5 chemical compositions, and meteorological data in Qingdao during 2015–2019 were collected. We used a time-stratified case-crossover design fitted with a conditional quasi-Poisson regression incorporated with distributed lag model to quantify the associations between PM1, PM2.5, and PM2.5 chemical compositions and MI mortality. Subgroup analyses were further implemented based on sex, age, and season. There were 36, 235 MI deaths in Qingdao during 2015–2019. The results of single-day lagged effects showed that PM1 (lag0 and lag1 days), PM2.5 (lag0 and lag1 days), sulfate (lag0 and lag1 days), nitrate (lag0 day), ammonium (lag0 and lag1 days), and black carbon (BC, lag0 and lag1 days) were positively related to an elevated risk of MI death. The cumulative effects of per interquartile range (IQR) rise in PM1, PM2.5, sulfate, nitrate, ammonium, and BC concentrations lasting for three days (lag02 day) were related to excess risks of 2.5% (95% confidence interval [CI]: 0.2%, 4.9%), 2.0% (0.1%, 3.9%), 2.2% (0.3%, 4.1%), 2.0% (0.1%, 3.9%), 2.0% (0.1%, 4.0%), and 2.1% (0.2%, 3.9%) for MI mortality, respectively. Significant effects of PM1, PM2.5, sulfate, and BC exposures on excess risks of MI mortality were observed in aging subpopulations or during the cold season. Short-term exposures to PM1, PM2.5, sulfate, nitrate, ammonium, and BC were linked to elevated risks of MI mortality. These results strengthen the case for implementing policies to reduce air pollution. Highlights: The effects of PM1 on MI mortality may be slightly higher than that of PM2.5 . Sulfate, nitrate, ammonium, and BC exposures may raise the risks of MI mortality. Significant effects of PM and constituent exposures were observed in aging subgroup. Clean heating policies should cover the scope of PM2.5 constituents in Qingdao.